Trash Compressor - Mohd Zulfanis, Amar; Mohamed Nor, Mohd Hadri; Norsahjatulnizam, Muhammad Fariz; Abdul Latif, Muhammad Yunus Nabil (Multidisciplinary Applied Research and Innovation, 2022)
The Trash Compressor permits a greater input of waste in a single plastic bag while preventing direct skin contact with the trash. The compressor adopts a manually operated system for simplicity using a handle and two holders to close the plastic and compress under on seamless motion, creating more room for additional discards after each compression. This operation allows consumers to restrict daily plastic usage which severs the constant flux of single-use plastic output where would eventually lead to plastic pollution in the long run. This project’s main focal point is the study and fabrication of a functional prototype of a domestic trash compressor with the appropriate mechanism in order the meet its objectives. The report scrutinizes the current on-going problems faced by the community regarding plastic plastic pollution and unsanitary landfills which inspires the idea of fabricating a working prototype which contributes against the root cause, single-use plastic consumption. The fabrication process as well the prototype performance test will also be discussed in this report. The aim for designing and fabricating this prototype is to weigh the merits and demerits of owning a domestic trash compressor through a performance analysis in terms of capacity ability and production cost.